A 30-Year-Old Male Patient of Miliary Tuberculosis Presented with Pancytopenia and Intracerebral Haemorrhage Mimicking Brain Tumor in MRI (Bangladesh Medical Journal, 2021)
Unlike to fever, pancytopenia is a rare hematological manifestations of tuberculosis and intracranial haemorrhage as well. Here we report a case of disseminated tuberculosis presented with pancytopenia and intracranial haemorrhage. The patient presented with prolonged pyrexia, weight loss and subsequently unconsciousness and convulsion. After the diagnosis of tuberculosis with pancytopenia and intracerebral haemorrhage flowed by convulsion, he was treated with category-1 standard anti-tubercular therapy and anticonvulsant. After completion of the anti-tubercular drug his fever completely subsided and gained weight and pancytopenia was improved. But he is still on anti-convulsant medication with good control of seizure.Bangladesh Med J. 2020 Jan; 49 (1): 51-54